The Impact Of The Village Fund Policy On Reducing Rural Criminal Incidents In Indonesia - Dyno Triandika Diputra; Putu Geniki Lavinia Natih (UNIVED Press, 2026)
This study aims to evaluate the impact of the Village Fund policy on reducing criminal incidents in Indonesian villages through improvements in environmental security systems. Utilizing a Difference-in-Differences (DiD) approach within a Poisson regression model, the study examines the effects of the Village Fund policy implementation across 36,889 villages during the 2011–2021 period. The analysis reveals that, following the implementation of the Village Fund policy, villages in the treatment group—characterized by relatively low environmental security systems—experienced a 0.937 times lower variation in criminal incidents compared to villages with high environmental security levels, with a statistical significance of 1%. These findings indicate that infrastructure development, community empowerment, and the enhancement of environmental security systems in more vulnerable areas contribute significantly to the reduction of criminal incidents in Indonesian villages.